Don"t be cruel (anymore): a look at the animal cruelty regimes of the United States and Brazil with a call for a new animal welfare agency. DOI 10.5935/2448-0517.20180010 - Cassuto, David N.; Eckhardt, Cayleigh (Juris Poiesis - Qualis A3, 2018)
In the United States and around the world, animals exploited for hu-man use suffer cruel and needless harm. The group bearing the brunt of this exploitation-agricultural animals-is routinely exempted from the largely ineffective and rarely enforced animal welfare and anti-cruelty regulations that exist today. This Article offers a comparative analysis of the agricultural animal welfare regimes of two countries with globally significant presence in the agriculture industry: the United States and Brazil. Even though the two countries approach agricultural animal welfare differently, they arrive at the same outcome: institutionalized indifference to animal suffering. To remedy the current regulatory structure, this Article proposes the creation of an independent federal agency-The Animal Welfare Agency ("AWA")-to regulate the safety and welfare of all animals, including those used in agriculture. The AWA could significantly reduce systemic animal cruelty in both the United States and Brazil and repre sent an important step toward inserting morality and ethics into our relationships with animals.